VOICE RECOGNITION AND PRONUNCIATION PRACTICE: HOW AI HELPS LEARNERS SPEAK MORE CLEARLY - Rajabova Fotimaxon O’tkirjonovna (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This article explores the role of artificial intelligence in improving pronunciation skills through the technology that recognises voice. It focuses on AI-powered tools like ELSA Speak, Google Assistant, and others that provide real-time feedback.